2020
DOI: 10.3390/jcm9030718
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Dose-Response Induced by Phytochemicals: Experimental Evidence

Abstract: Many phytochemicals demonstrate nonmonotonic dose/concentration-response termed biphasic dose-response and are considered to be hormetic compounds, i.e., they induce biologically opposite effects at different doses. In numerous articles the hormetic nature of phytochemicals is declared, however, no experimental evidence is provided. Our aim was to present the overview of the reports in which phytochemical-induced biphasic dose-response is experimentally proven. Hence, we included in the current review only art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 92 publications
(194 reference statements)
9
41
1
Order By: Relevance
“…One possible explanation is that higher concentrations of EtBr may have triggered a defense mechanism, such as efflux of EtBr or upregulated DNA repair pathways, that may explain the lower number of canavanine-resistant colonies. Such an explanation would be consistent with hormesis [36,37]. Nonetheless, the number of canavanine-resistant colonies from yeast grown in EtBr from 0.1 to 10 μg EtBr/L was significantly more than control ( Fig 2B ), demonstrating that we could detect the mutagenic potential of yeast even at concentrations lower than the limit of detection for the Ames test.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…One possible explanation is that higher concentrations of EtBr may have triggered a defense mechanism, such as efflux of EtBr or upregulated DNA repair pathways, that may explain the lower number of canavanine-resistant colonies. Such an explanation would be consistent with hormesis [36,37]. Nonetheless, the number of canavanine-resistant colonies from yeast grown in EtBr from 0.1 to 10 μg EtBr/L was significantly more than control ( Fig 2B ), demonstrating that we could detect the mutagenic potential of yeast even at concentrations lower than the limit of detection for the Ames test.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, we observed that the lower concentrations of EtBr (0.1 and 1.0 μg EtBr/L) produced higher numbers of canavanine-resistant colonies than the highest concentration of EtBr (10 μg EtBr/L), a biphasic response consistent with hormesis. Briefly, hormesis is when a low dose of a toxin produces a higher effect than a lower dose, perhaps because the higher dose induces protective responses not triggered by the lower dose [36,37]. This observation was reproducible in two more independent runs of the parallel chemostats (S1 C and D Figs ).…”
Section: Resultsmentioning
confidence: 79%
“…Hormesis is a phenomenon of biphasic dose response in which a compound usually exhibits stimulatory or beneficial effects at low doses and inhibitory or toxic effects at high doses [ 32 , 33 , 34 , 35 ]. Hormetic effect should be considered in cancer therapy in order to optimize treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hormesis, the low dose stress modulatory effect, describes how phytochemicals (including many other agents) are bimodal in their function often acting positively at a significantly lower dose and acting negatively at higher doses [78][79][80][81] . There is the idea that early life stressors can lead to resilience in later life [78] , and if thought of in the context of dietary factors then early exposure to chemopreventive compounds might condition the body for greater resilience or make it refractory to oncogenic stimuli [80] .…”
Section: Hormetic Effects May Govern the Efficacy Of Phytochemicals Amentioning
confidence: 99%
“…Hormesis, the low dose stress modulatory effect, describes how phytochemicals (including many other agents) are bimodal in their function often acting positively at a significantly lower dose and acting negatively at higher doses [78][79][80][81] . There is the idea that early life stressors can lead to resilience in later life [78] , and if thought of in the context of dietary factors then early exposure to chemopreventive compounds might condition the body for greater resilience or make it refractory to oncogenic stimuli [80] . At another cellular level, acknowledging that mitochondria are absolutely essential for life, mitohormesis (an adaptive stress response) defines a biological response where reduction in mitochondrial stress can lead to significant increments in health and vitality proscribing what is felt to be the anti-aging paradigm [3,82] .…”
Section: Hormetic Effects May Govern the Efficacy Of Phytochemicals Amentioning
confidence: 99%